Zavedení Business Continuity and Disaster Recovery strategie - Solár, Matúš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Táto diplomová práca sa zaoberá a analyzuje problematiku stratégie kontinuity činností a obnovy po katastrofe. Navrhuje možné riešenia a ich praktickú implementáciu v reálnom prostredí banky. Súčasťou práce sú teoretické východiská, analýza súčasného stavu, ktorá vypovedá o nedostatkoch v danom prostredí a v neposlednom rade návrhy na zavedenie samotnej stratégie.

This master thesis deals and analyzes the problems in the area of Business Continuity and Disaster Recovery strategy. It proposes a possible solutions, its practical implementation in the real environment of bank. Part of this work speaks about theoretical background, second part of this work analyzes the current situation, which describes the deficiencies in the given directions and in the end are explained my practical advices for implementation of the Business Continuity and Disaster Recovery strategy.
Business Continuity and Disaster Recovery Strategy Implementation
Keywords: riadenie kontinuity činností; obnova po katastrofe; analýza dopadu na business; testovanie; plán kontinuity činností; plán obnovy po katastrofe; kritická situácia; katastrofa; riziko; business continuity; disaster recovery; business impact analysis; testing; business continuity plan; disaster recovery plan; criticall situation; disaster; risk